(x-4)^3

=(x-4)2(x-4)=(x2-8x+16)(x-4)=x3-4x2-8x2+32x+16x-64= x3-12x2+48x-64

Answered by Pavel B. Maths tutor

2708 Views

See similar Maths A Level tutors

Related Maths A Level answers

All answers ▸

A circle is given by the equation x^2+y^2-20x-24y+195=0. Draw this circle.


OCR C2 2015 Question 8: (a) Use logarithms to solve the equation 2^(n-3) = 18,000 , giving your answer correct to 3 significant figures. (b) Solve the simultaneous equations log2(x) + log2(y) = 8 & log2(x^2/y) = 7.


x^3 + 3x^2 + 2x + 12


If the quadratic equation kx^2+kx+1=0 has no real roots, what values of k are possible?


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences